C-terminus Proteolysis and Palmitoylation Cooperate for Optimal Plasma Membrane Localization of RasA in Aspergillus fumigatus - Al Abdallah, Qusai; Martin-Vicente, Adela; Souza, Ana Camila Oliveira; Ge, Wenbo; Fortwendel, Jarrod R. (Frontiers in Microbiology, 2018)
RasA is a major regulator of fungal morphogenesis and virulence in A. fumigatus. The proper localization of RasA to the plasma membrane is essential for the formation of invasive hyphae during infection. In yeast, the localization of Ras2p to the plasma membrane is orchestrated by several post-translational modifications (PTM) at the C-terminal CAAX box that are thought to occur in sequential order. These PTMs include: 1) CAAX motif farnesylation by the farnesyltransferase complex composed of Ram1p and Ram2p; 2) proteolysis of the -AAX residues by Rce1p or Ste24p; 3) methylation of the remaining prenylated cysteine residue by Ste14p, and; 4) palmitoylation at a single conserved cysteine residue mediated by the Erf2p/Erf4p palmitoyltransferase. We previously reported that homologues of each RasA PTM enzyme are conserved in A. fumigatus. Additionally, we delineated a major role for protein farnesylation in A. fumigatus growth and virulence. In this work, we characterize the post-prenylation processing enzymes of RasA in A. fumigatus. The genes encoding the RasA post-prenylation enzymes were first deleted and examined for their roles in growth and regulation of RasA. Only when strains lacked cppB, the A. fumigatus homologue of yeast RCE1, there was a significant reduction in fungal growth and conidial germination. In addition, cppB-deletion mutants displayed hypersensitivity to the cell wall-perturbing agents Calcofluor White and Congo Red and the cell wall biosynthesis inhibitor Caspofungin. In contrast to the previously published data in yeast, the deletion of post-prenylation modifying enzymes did not alter the plasma membrane localization or activation of RasA. To delineate the molecular mechanisms underlying these differences, we investigated the interplay between dual-palmitoylation of the RasA hypervariable region and CAAX proteolysis for stabilization of RasA at the plasma membrane. Our data indicate that, in the absence of proper CAAX proteolysis, RasA accumulation at the plasma membrane is stabilized by dual palmitoyl groups on the dual cysteine residues. Therefore, we conclude CAAX proteolysis and dual-palmitoylation of the hypervariable region is important for maintaining a stable attachment association of RasA with the plasma membrane to support optimal fungal growth and development.